Early Cretaceous decapod Crustacea from the Neuquén Basin, west-central Argentina - Aguirre-Urreta, Maria Beatriz (2003)
Marine deposits of the Neuquén Basin of west-central Argentina (southern South America) are richly fossiliferous; its Mesozoic invertebrate faunas, represented mostly by molluscs, have been extensively studied since the nineteenth century. However, Early Cretaceous decapod crustaceans are far less known, although part of the systematic framework has been published (Aguirre-Urreta, 1989). The aim of the present note is to provide updated information based on ongoing research into the systematics and taphonomy of this crustacean group in the Neuquén Basin.